2009
DOI: 10.1007/s10565-009-9146-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphological damages of a glyphosate-treated human keratinocyte cell line revealed by a micro- to nanoscale microscopic investigation

Abstract: Among the molecules to which the human skin is exposed, glyphosate is used as an herbicide. Glyphosate has been shown to induce in vitro cutaneous cytotoxic effects, concomitant with oxidative disorders. In this following study, we focused on dynamic events of the loss of HaCaT cell integrity appearing after a glyphosate treatment. In these conditions, we showed that glyphosate is able to disrupt HaCaT cells and to induce intracellular oxidative cascade. In this aim, we optimized the conditions of cell treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 26 publications
4
12
0
4
Order By: Relevance
“…Previously, in vitro studies had addressed that glyphosate facilitates oxidative stress [37, 40], and in this study, we confirmed that glyphosate treated HaCaT cells differ from vehicle control cells in the oxidative stress level. The levels of ROS production in glyphosate, TPA, and H 2 O 2 treated cells were significantly higher than those found in control cells (Figure 4(a)).…”
Section: Discussionsupporting
confidence: 84%
“…Previously, in vitro studies had addressed that glyphosate facilitates oxidative stress [37, 40], and in this study, we confirmed that glyphosate treated HaCaT cells differ from vehicle control cells in the oxidative stress level. The levels of ROS production in glyphosate, TPA, and H 2 O 2 treated cells were significantly higher than those found in control cells (Figure 4(a)).…”
Section: Discussionsupporting
confidence: 84%
“…Also, the excessive production of ROS can cause immunosuppression (Lecchi, Rota, Vitali, Ceciliani, & Lacetera, ). Additionally, glyphosate can cause the disorganization of the cytoskeleton and alter cell integrity (Elie‐Caille et al, ), which is likely to cause structural damage in the liver and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Glyphosate has also been shown to be able to disrupt regenerative diploid (DIMF) and triploid fin cell lines from the Oriental weather loach (Misgurnus anguillicaudatus) with cytotoxicity of LC 50 = 0.315 and 0.372 mg/ml, respectively. It also was found to induce DNA damage (micronucleus formation), cell damages (chromatin condensation, nucleus distortion, broken, and reduced endoplasmic reticulum, mitochondria and ribosomes) and apoptosis , intracellular oxidative cascade, morphological modifications, and apoptosis (Elie-Caille et al, 2010) caused by oxidative stress due to mitochondrial membrane potential disruption (Heu et al, 2012b) and cell morphological changes (Heu et al, 2012a). In addition to detection of decreased cell viability (tested in the above examples), cytotoxicity has been tested on other end points as well, including mutagenicity within the same range of toxicity (EC 50 = 0.6-0.9 mg/ml) for human epithelial type 2 cells (Hep-2) as occurs for human cervical cancer cell (HeLa) contaminant (Mañas et al, 2009), human fibroblast cells (GM38) (Monroy et al, 2005), and human fibrosarcoma cells (HT1080) (Monroy et al, 2005).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…Roundup Transorb R exerted cytotoxicity on a zebrafish (Danio rerio) hepatocyte cell line ZF-L at concentrations as low as 0.068-0.27 µg/ml (corresponding to glyphosate concentrations of 0.033-0.13 µg/ml), due mostly to lysosomal instability and inhibition of mitochondrial function, and slightly to impaired cell membrane integrity. Synergistic detrimental effects were observed when Roundup Transorb R was applied with an insecticide formulation (Furadan 350 FIGURE 3 | In vitro cytotoxicity of glyphosate (light columns) and its formulated preparation Roundup ® (dark columns) on various cell lines Raji: human hematopoietic Raji (Epstein-Barr virus transformed human lymphocyte) cells (Townsend et al, 2017), DIMF, diploid fin cell line from the Oriental weather loach Misgurnus anguillicaudatus ; HaCaT, human epithelial keratinocyte cells (Elie-Caille et al, 2010); NE-4C, murine stem cell-like neuroectodermal cells ; Hep-2, human epithelial type 2 (HeLa contaminant) cells (Mañas et al, 2009); GM38, human fibroblast cells (Monroy et al, 2005); HT1080, human fibrosarcoma cells (Monroy et al, 2005); HUVEC, primary neonate human umbilical vein endothelial cells (Benachour et al, 2007;Benachour and Séralini, 2009;Gasnier et al, 2009); HEK293, embryonic kidney cells (Benachour et al, 2007;Benachour and Séralini, 2009;Gasnier et al, 2009;Mesnage et al, 2013a); MC3T3-E1, murine osteoblast precursor cells (Farkas et al, 2018); HepG2, human hepatoma cells (Benachour et al, 2007;Benachour and Séralini, 2009;Gasnier et al, 2009); JAr, human chorioplacental cells (Young et al, 2015); JEG3, human choriocarcinoma cells (Benachour et al, 2007;Benachour and Séralini, 2009;Gasnier et al, 2009;Mesnage et al, 2013aMesnage et al, , 2017a. Plain and grid column patterns indicate cytotoxicity detected by MTT test and mutagenicity tests, respectively.…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%